2022
DOI: 10.3389/fmed.2022.822194
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association of Periodontal Diseases With Helicobacter pylori Gastric Infection: A Systematic Review and Meta-Analysis

Abstract: Some research has suggested that dental plaque and saliva could be reservoirs of Helicobacter pylori (H. pylori) and be capable of infecting or re-infecting the gastric mucosa after eradication, with certain studies showing a significant association between PD and gastric infection by this bacterium. An electronic search was performed in PubMed, EMBASE, and Web of Science databases with the terms “Helicobacter pylori AND periodontal diseases”; “Helicobacter pylori AND gingivitis”; “Helicobacter pylori AND chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Moreover, although there were some studies demonstrating that H. pylori in the oral cavity affected the outcome of eradication therapy [10], and that adjunctive periodontal therapy could enhance the efficiency of H. pylori treatment [22, 23], there is still no evidence that the recurrence after eradication therapy of gastric H. pylori is caused by oral H. pylori . In their systematic review and meta-analysis, López-Valverde et al reported that there is no clear evidence that H. pylori present in oral bacterial biofilm causes gastric infections and vice versa [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although there were some studies demonstrating that H. pylori in the oral cavity affected the outcome of eradication therapy [10], and that adjunctive periodontal therapy could enhance the efficiency of H. pylori treatment [22, 23], there is still no evidence that the recurrence after eradication therapy of gastric H. pylori is caused by oral H. pylori . In their systematic review and meta-analysis, López-Valverde et al reported that there is no clear evidence that H. pylori present in oral bacterial biofilm causes gastric infections and vice versa [24].…”
Section: Introductionmentioning
confidence: 99%